Certolizumab: efficacy and safety profile of a novel pegylatedTNF-alpha blocking agent - Lubrano, E.; Spadaro, A. (Acta Biomedica Atenei Parmensis, 2011)
The treatment of Rheumatoid Arthritis (RA) has changed since the introduction of biological agents. In particular, the anti Tumor Necrosis Factor (TNF)-α molecules have been the first group of drugs showing a good efficacy and safety profile. Among these, a new anti TNF-α antibody has been recently indicated for the treatment of RA: certolizumab pegol (CZP). In the main clinical trials this new pegylated anti TNF-α has shown to be efficacious on clinical, functional and prevention of structural damage in patients with active RA and with inadequate response to traditional disease modifying drugs, including methotrexate. Moreover CZP showed to be well tolerated and most adverse events occurred were mild or moderate. Therefore, results obtained showed that this new molecule can play a role in the treatment of RA.